Blue deficiency in patients with diabetis mellitus without retinopathy - its clincial implications - Sharanjeet- Kaur, (Universiti Kebangsaan Malaysia, 1996)
This study was conducted for 3 main purposes: 1) to determine if there was blue colour deficiency amongst diabetes mellitus (IDDM and NIDDM) patients without retinopathy, 2) to determine if the Dl5 test could be used to detect any colour vision defects amongst diabetics without retinopathy (all previous workers have used FM 100-Hue), and 3) to assess the performance of diabetics without retinopathy in detecting correct colour changes with the urine strip test. Thirty eight non-insulin dependent diabetes mellitus (NIDDM) and 30 insulin-dependent diabetes mellitus (IDDM) patients without retinopathy participated in this study. A control group of 23 normal subjects were also included in the study. Dl5 colour vision test was performed under daylight conditions. Colour dependent urine glucose test (Glukotest) was also performed on all subjects. The study showed that 47.1% of diabetics (47.4% NIDDM and 46.7% IDDM patients) without retinopathy had a blue colour deficiency. Amongst the diabetics with a blue colour deficiency, 25% of diabetics (22% of NIDDM and 28.6% of IDDM patients) failed to accurately match the strip colour with the comparison chart on the bottle.